2022
DOI: 10.12688/wellcomeopenres.17143.3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for SARS-CoV-2 seroprevalence following the first pandemic wave in UK healthcare workers in a large NHS Foundation Trust

Abstract: Background: We aimed to measure SARS-CoV-2 seroprevalence in a cohort of healthcare workers (HCWs) during the first UK wave of the COVID-19 pandemic, explore risk factors associated with infection, and investigate the impact of antibody titres on assay sensitivity. Methods: HCWs at Sheffield Teaching Hospitals NHS Foundation Trust were prospectively enrolled and sampled at two time points. We developed an in-house ELISA for testing participant serum for SARS-CoV-2 IgG and IgA reactivity against Spike and Nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Using HCM, we observed a statistically significant difference in signal intensity for N and S antibodies between pre-pandemic and SARS-CoV-2-positive samples ( Figures 2 A and 2C). As previously reported, 27 we found that IgG levels were significantly elevated for N and S in patients hospitalized after SARS-CoV-2 infection (inpatient) compared to non-hospitalized individuals (outpatient), with these trends also seen in ELISA absorbances for the sample sets ( Figures S4 A, S4B, S4E, and S4F). ELISA-based detection of N or S IgG in SARS-CoV-2-positive samples had marginally higher sensitivity than HCM when specificity was fixed at 100% ( Figure 2 B, N ELISA (185/196, 94.4%) vs. N HCM (182/196, 92.9%), Figure 2 D, S ELISA (195/196, 99.5%) vs. S HCM (192/196, 98.0%)), Tables S1 and S2 ) with a greater number of samples from COVID-19 inpatients containing detectable N or S IgG ( Figures S4 C, S4D, S4G, and S4H, Tables S1 and S2 ).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Using HCM, we observed a statistically significant difference in signal intensity for N and S antibodies between pre-pandemic and SARS-CoV-2-positive samples ( Figures 2 A and 2C). As previously reported, 27 we found that IgG levels were significantly elevated for N and S in patients hospitalized after SARS-CoV-2 infection (inpatient) compared to non-hospitalized individuals (outpatient), with these trends also seen in ELISA absorbances for the sample sets ( Figures S4 A, S4B, S4E, and S4F). ELISA-based detection of N or S IgG in SARS-CoV-2-positive samples had marginally higher sensitivity than HCM when specificity was fixed at 100% ( Figure 2 B, N ELISA (185/196, 94.4%) vs. N HCM (182/196, 92.9%), Figure 2 D, S ELISA (195/196, 99.5%) vs. S HCM (192/196, 98.0%)), Tables S1 and S2 ) with a greater number of samples from COVID-19 inpatients containing detectable N or S IgG ( Figures S4 C, S4D, S4G, and S4H, Tables S1 and S2 ).…”
Section: Resultssupporting
confidence: 87%
“…Plasma samples used were from healthcare workers (HCWs) recruited at Sheffield Teaching Hospitals NHS Foundation Trust (STH) as part of the COVID-19 Humoral Immune Responses in front-line healthcare workers (HCWs) study (HERO), sampled in May and June 2020. 27 Further longitudinal plasma samples from HCWs were used from a prospective, observational, cohort study (PITCH), where in Sheffield, participants were recruited under the Sheffield Teaching Hospitals (STH) Observational Study of Patients with Pulmonary Hypertension, Cardiovascular Disease and other Respiratory Disease (STH-Obs). 44 , 45 Regulatory approval was provided by HRA and Health and Care Research Wales (HERO - 20/HRA/2180), and the Yorkshire and Humber – Sheffield Research Ethics Committee (STHObs - 18/YH/0441).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleocapsid IgG was assessed using an ELISA as previously described (36). High-binding 96-well ELISA plates (Immulon 4HBX; Thermo Scientific, 6405) were coated overnight at 4°C with 50 µL/well full-length untagged nucleocapsid protein produced in E. coli (Uniprot ID P0DTC9 (NCAP_SARS2), diluted to 2 µg/mL in 7.4 pH phosphate buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…To allow quantification of antibody concentration, we included a 12-step standard curve consisting of sera pooled from convalescent SARS-CoV-2-confirmed patients, calibrated to the WHO International Standard for anti-SARS-CoV-2 immunoglobulin (NIBSC, 20/136), with results reported in binding antibody units/mL (BAU/mL). Samples that were considered negative based on previously determined thresholds (36) were assigned a value of 1.04 BAU/mL, which was half the value of the lowest point on the standard curve.…”
Section: Methodsmentioning
confidence: 99%